A carbon fiber material printing template and manufacturing method thereof
By using the printing template of the ceramic outer frame and the inner net of the carbon fiber composite material, the problem of insufficient tensile resistance in the prior art is solved, high tensile strength and wear resistance are achieved, and the solder paste offset and elongation are reduced. The overall performance of the printing template is improved.
Patent Information
- Application Number
- CN202410632797.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-05-21
AI Technical Summary
The existing printing template materials cannot meet the high precision requirements for ultra-small components manufacturing, and they are insufficient in tensile resistance and wear resistance, which is prone to defects such as cracking, reduced printing times and solder paste bias, affecting product quality.
Using a printing template with ceramic outer frame and carbon fiber composite inner net, a carbon fiber material printing template with high tensile strength, wear resistance and hydrophobicity is prepared by combining zirconia ceramics and polyimide-PDVB nanocomposites. .
It improves the tensile resistance and wear resistance of the printed template, reduces the solder paste offset and elongation, enhances the self-cleaning ability, and significantly improves the overall performance of the printed template.
Smart Images

Figure CN118510165B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printing templates, and in particular to a carbon fiber material printing template and a manufacturing method thereof. Background Art
[0002] With the continuous reduction in the size of electronic products and the demand for high-precision integration, the application of ultra-small components such as 01005 packaged components is becoming more and more extensive, and the requirements for manufacturing processes are becoming higher and higher. The solder paste is transferred to the pads of the electronic circuit board through the opening of the printing template under the movement of the scraper. However, most of the existing printing templates are simple in design, and most of them are made of stainless steel or nickel-plated materials. The templates are thick and cannot meet the manufacturing requirements of ultra-small components. In addition, the templates often crack and reduce the number of printing times and life. The printed solder paste is easily displaced, which affects the product quality. In addition, the tensile strength is weak. The patent with application number 201410417880.2 discloses an SMT printing template, including an anti-scratch layer, which is made of steel and arranged on the surface of the SMT printing template. Below the anti-scratch layer is a composite material layer, which is made of a mixture of polymer materials and photosensitive materials. The invention is made of multiple materials in multiple layers, resulting in its thickness being too thick, which cannot meet the manufacturing process requirements of ultra-small components. Patent No. 200680034789.6 discloses a printing template and a coating method of a surface mount technology process. The metal template body of the printing template is provided with a thin coating made of a metal alkoxide coating material. The surface energy of the coating is reduced by chemically bonding at least one organic component, thereby reducing the size of the pores, but its tensile strength is weak and the flatness is poor. Therefore, it is of great significance to develop a carbon fiber material printing template with high tensile strength, strong wear resistance, strong hydrophobic outer frame and inner net, strong self-cleaning performance, and easy demoulding of solder paste. Summary of the invention
[0003] The purpose of the present invention is to solve the above deficiencies in the prior art and to propose a carbon fiber material printing template and a manufacturing method thereof.
[0004] A carbon fiber material printing template comprises a ceramic outer frame and a carbon fiber composite material inner net.
[0005] Furthermore, the ceramic outer frame is made of zirconia ceramic and polyimide-PDVB nanocomposite material.
[0006] Furthermore, the preparation method of the ceramic outer frame is to apply the suspension on the zirconia ceramic, heat the reaction to obtain the ceramic containing polyimide, ultrasonically mix divinylbenzene, azoisobutyronitrile and ethyl acetate to obtain a mixed solution, and put the ceramic containing polyimide into the mixed solution to obtain the ceramic containing polyimide-PDVB nanocomposite material.
[0007] Furthermore, the preparation method of the carbon fiber composite material inner net is to laser cut the carbon fiber plate containing the polyimide-PDVB composite material into carbon fiber warp and weft lines, lay them flat, and press the intersections of the carbon fiber warp and weft lines.
[0008] Furthermore, the polyimide-PDVB nanocomposite material is prepared from the following raw materials: 2,2′-bis(trifluoromethyl)benzidine, dimethylacetamide, 4,4′-(hexafluoroisopropylidene)diphthalic anhydride, [(3-triethoxysilyl)propyl]succinic anhydride, tetraethyl orthosilicate, additives, divinylbenzene, azoisobutyronitrile and ethyl acetate;
[0009] Preferably, the additives are nanocarbon and graphene;
[0010] Preferably, the auxiliary agent comprises 1-3 parts of nano-carbon and 1-3 parts of graphene by weight.
[0011] Furthermore, the carbon fiber plate containing the polyimide-PDVB nanocomposite material is prepared from the following raw materials in parts by weight: 5-15 parts of 2,2′-bis(trifluoromethyl)benzidine, 90-180 parts of dimethylacetamide, 10-20 parts of 4,4′-(hexafluoroisopropylidene)diphthalic anhydride, 1-5 parts of [(3-triethoxysilyl)propyl]succinic anhydride, 1-5 parts of tetraethyl orthosilicate, 2-6 parts of additives, 1 part of divinylbenzene, 0.06 parts of azoisobutyronitrile and 45 parts of ethyl acetate.
[0012] Furthermore, the preparation method of the carbon fiber board containing the polyimide-PDVB nanocomposite material is as follows:
[0013] 2,2′-bis(trifluoromethyl)benzidine and dimethylacetamide are stirred with argon at 25° C., 4,4′-(hexafluoroisopropyl)diphthalic anhydride is added to a flask, the resulting solution is stirred with argon at 25° C. to prepare a polyamic acid solution, [(3-triethoxysilyl)propyl]succinic anhydride is added, and the resultant is stirred to synthesize [(3-triethoxysilyl)propyl]succinic anhydride end-capped polyamic acid, tetraethyl orthosilicate, ethanol and ammonia solution are added, and silica sol is obtained by stirring, and the silica sol is added to the end-capped polyamic acid solution, and a suspension is obtained by stirring, and an auxiliary agent is added to the suspension, and the suspension is coated on a carbon fiber board, and heated to obtain a carbon fiber board containing an auxiliary agent (nanocarbon, graphene) polyimide, and divinylbenzene, azoisobutyronitrile and ethyl acetate are ultrasonically mixed to obtain a mixed solution, and the carbon fiber board containing polyimide is placed in the mixed solution and reacted in a reactor to obtain a carbon fiber board containing a polyimide-PDVB composite material.
[0014] Further, the 2,2′-bis(trifluoromethyl)benzidine and dimethylacetamide are stirred at 25° C. with argon for 20-40 minutes;
[0015] Preferably, tetraethyl orthosilicate, ethanol and ammonia solution are added with stirring at a temperature of 50-60° C. for 1-2 hours;
[0016] Preferably, the silica sol is added to the end cap polyamic acid solution with stirring at a temperature of 50-60° C. for 2-4 hours.
[0017] Furthermore, the thickness of the suspension coated on the carbon fiber plate is 1-3 μm.
[0018] Furthermore, a carbon fiber plate containing polyimide is placed in the mixed solution and the reaction temperature is 100-150° C. to obtain a carbon fiber plate containing a polyimide-PDVB composite material.
[0019] The carbon fiber material printing template and the manufacturing method thereof proposed by the present invention have the following beneficial effects:
[0020] 1. Polyimide has strong hydrophobicity and wear resistance. Polydivinylbenzene PDVB is added to polyimide materials as an improvement additive. Under the appropriate proportion, it will not affect the hydrophobicity, and can make the formed coating more wear-resistant and reduce costs;
[0021] 2. The polyimide-PDVB nanocomposite material as a coating is not only highly hydrophobic and self-cleaning, but also beneficial to the cleaning of residual solder paste. The components of polyimide-PDVB work synergistically, and under certain proportions and dispersion conditions, it can reduce the solder paste offset and the elongation of the carbon fiber material printing template, and can also enhance the wear resistance of the printing template, which is better than the traditional printing templates sold on the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The scanning electron microscope image and the corresponding surface contact angle of Comparative Example 2, the scale is 500um;
[0023] Figure 2 The scanning electron microscope image and the corresponding surface contact angle of the carbon fiber plate containing the polyimide-PDVB nanocomposite material in Example 1, the scale is 500um;
[0024] Figure 3 This is a finished product image of the carbon fiber material printing template of Example 1. DETAILED DESCRIPTION
[0025] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0026] Unless otherwise specified, the examples and comparative examples are parallel tests with the same components, component contents, preparation steps and preparation parameters. The experimental methods in the following examples are conventional methods unless otherwise specified; the parts in the experiments are parts by weight unless otherwise specified; the test materials used in the following examples are analytical reagents (AR) unless otherwise specified, which are purchased from commercial channels.
[0027] 4,4′-(Hexafluoroisopropylidene)diphthalic anhydride (6FDA), tetraethyl orthosilicate (TEOS), aqueous ammonia solution (32 wt%), and triethoxy-1H,1H,2H,2H-perfluorodecylsilane (TEFDS) were purchased from Merck Korea (Seoul, South Korea). [(3-Triethoxysilyl)propyl]succinic anhydride (3TPA) and 2,2′-bis(trifluoromethyl)benzidine (TFMB) were purchased from Tokyo Chemical Industry (Tokyo, Japan) and used as received. Dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), and industrial-grade ethanol were purchased from Ducksan Pure Chemical (Seoul, South Korea) and used as received; zirconia ceramics with a size of 300 mm × 300 mm and a thickness of 0.03 mm were purchased from Xinghongfei Electronic Technology Co., Ltd., Foshan, China. 3K carbon fiber plate was purchased from Shenzhen Dongbohai Technology Co., Ltd., item number 8010. Graphene was purchased from Nanjing Jicang Nanotechnology Co., Ltd., submicron graphene powder, thickness 1 nm, purity 98%, specific surface area 500 m2 / g, oxygen content 0.5%; nanocarbon was purchased from Nanjing Jicang Nanotechnology Co., Ltd., nitrogen-doped porous nanocarbon, specific surface area 595 m2 / g, particle size 200 nm, nitrogen content 3%, pore size 7 nm, hydroxyl-terminated polydimethylsiloxane (PDMS, AR, M=1000, Guangzhou Jucheng Zhaoye Silicone Materials Co., Ltd.).
[0028] Embodiment 1:
[0029] Preparation of carbon fiber sheet containing polyimide-PDVB nanocomposite: 12 parts of 2,2′-bis(trifluoromethyl)benzidine and 170 parts of dimethylacetamide were stirred at room temperature with argon for 30 minutes. 17 parts of 4,4′-(hexafluoroisopropylidene)diphthalic anhydride were added, and the resulting solution was stirred at room temperature with argon for 3 hours to prepare a polyamic acid solution. After adding 1 part of [(3-triethoxysilyl)propyl]succinic anhydride, it was stirred for 1 hour to synthesize [(3-triethoxysilyl)propyl]succinic anhydride end-capped polyamic acid. To another double-necked round-bottom flask with a reflux condenser, 2 parts of tetraethyl orthosilicate, 16 parts of ethanol and 2 parts of ammonia solution were added. The mixture was stirred at 60°C for 1 hour to obtain a silica sol. 10 parts of the silica sol were added to 200 parts of the end-capped polyamic acid solution and stirred at 50°C for 3 hours to obtain a suspension. Add 3 parts of nanocarbon and 1 part of graphite to 10 parts of the suspension, apply the suspension on a carbon fiber board with a thickness of 3 μm, heat at 220°C for 2 hours to obtain a carbon fiber board containing polyimide with additives (nanocarbon, graphite), ultrasonically mix 1 part of divinylbenzene, 0.06 parts of azoisobutyronitrile and 45 parts of ethyl acetate for 30 minutes to obtain a mixed solution, put the carbon fiber board containing polyimide into the mixed solution and react in a reactor at 100°C for 30 hours to obtain a carbon fiber board containing a polyimide-PDVB composite material.
[0030] Preparation of hydrophobic ceramics: The suspension prepared above is coated on zirconia ceramics with a thickness of 3 μm, and heated at 250°C for 3 hours to obtain ceramics containing polyimide, 1 part of divinylbenzene, 0.06 parts of azoisobutyronitrile and 45 parts of ethyl acetate are ultrasonically mixed for 30 minutes to obtain a mixed solution, and the ceramics containing polyimide are placed in the mixed solution and reacted in a reactor at 100°C for 30 hours to obtain hydrophobic ceramics.
[0031] The material is cut with a high-precision UV picosecond laser with a laser power of 30W, and cut into 7-micron diameter carbon fiber warp and weft lines, which are then laid flat. A high-precision laminating device with a laminating head with a tiny laminating surface is used to apply pressure at the intersection of the carbon fiber warp and weft lines to make them fit tightly together. The hydrophobic ceramic is then pressed with the carbon fiber inner net to make a carbon fiber material printing template.
[0032] Embodiment 2:
[0033] Preparation of carbon fiber sheet containing polyimide-PDVB nanocomposite: 12 parts of 2,2′-bis(trifluoromethyl)benzidine and 170 parts of dimethylacetamide were stirred at 25°C with argon for 30 minutes. 17 parts of 4,4′-(hexafluoroisopropylidene)diphthalic anhydride were added, and the resulting solution was stirred at 25°C with argon for 3 hours to prepare a polyamic acid solution. After adding 1 part of [(3-triethoxysilyl)propyl]succinic anhydride, it was stirred for 1 hour to synthesize [(3-triethoxysilyl)propyl]succinic anhydride end-capped polyamic acid. 2 parts of tetraethyl orthosilicate, 16 parts of ethanol and 2 parts of ammonia solution were added to another two-necked round-bottom flask with a reflux condenser. The mixture was stirred at 60°C for 1 hour to obtain a silica sol. 10 parts of the silica sol were added to 200 parts of the end-capped polyamic acid solution and stirred at 50°C for 3 hours to obtain a suspension. The suspension is coated on a carbon fiber board with a thickness of 1 μm, heated at 220°C for 2 hours to remove the residual solvent and simultaneously perform imidization, 1 part of nanocarbon and 1 part of graphene are added to 6 parts of the suspension, the suspension is coated on a carbon fiber board with a thickness of 3 μm, and heated at 220°C for 2 hours to obtain a carbon fiber board containing polyimide containing additives (nanocarbon, graphene), 1 part of divinylbenzene, 0.06 parts of azoisobutyronitrile and 45 parts of ethyl acetate are ultrasonically mixed for 30 minutes to obtain a mixed solution, the carbon fiber board containing polyimide is placed in the mixed solution and reacted in a reactor at 100°C for 30 hours to obtain a carbon fiber board containing a polyimide-PDVB composite material.
[0034] The method for preparing hydrophobic ceramics and the method for printing carbon fiber material templates are the same as those in Example 1.
[0035] Embodiment 3:
[0036] Preparation of carbon fiber sheet containing polyimide-PDVB nanocomposite: 12 parts of 2,2′-bis(trifluoromethyl)benzidine and 170 parts of dimethylacetamide were stirred at 25°C with argon for 30 minutes. 17 parts of 4,4′-(hexafluoroisopropylidene)diphthalic anhydride were added, and the resulting solution was stirred at 25°C with argon for 3 hours to prepare a polyamic acid solution. After adding 1 part of [(3-triethoxysilyl)propyl]succinic anhydride, it was stirred for 1 hour to synthesize [(3-triethoxysilyl)propyl]succinic anhydride end-capped polyamic acid. 2 parts of tetraethyl orthosilicate, 16 parts of ethanol and 2 parts of ammonia solution were added to another two-necked round-bottom flask with a reflux condenser. The mixture was stirred at 60°C for 1 hour to obtain a silica sol. 10 parts of the silica sol were added to 200 parts of the end-capped polyamic acid solution and stirred at 50°C for 3 hours to obtain a suspension. The suspension is coated on a carbon fiber board with a thickness of 2 μm, heated at 220°C for 2 hours to remove the residual solvent and simultaneously perform imidization, 2 parts of nanocarbon and 3 parts of graphene are added to 8 parts of the suspension, the suspension is coated on a carbon fiber board with a thickness of 3 μm, and heated at 220°C for 2 hours to obtain a carbon fiber board containing polyimide containing additives (nanocarbon, graphene), 1 part of divinylbenzene, 0.06 parts of azoisobutyronitrile and 45 parts of ethyl acetate are ultrasonically mixed for 30 minutes to obtain a mixed solution, the carbon fiber board containing polyimide is placed in the mixed solution and reacted in a reactor at 150°C for 30 hours to obtain a carbon fiber board containing a polyimide-PDVB composite material.
[0037] The method for preparing hydrophobic ceramics and the method for printing carbon fiber material templates are the same as those in Example 1.
[0038] Comparative Example 1: The difference from Example 1 is that zirconia ceramics without adding polyimide-PDVB nanocomposite materials are directly used, and the other conditions are the same.
[0039] Comparative Example 2: The difference from Example 1 is that the polyimide-PDVB nanocomposite material is missing, and a commercially available carbon fiber board is directly used, and the other parts are the same.
[0040] Comparative Example 3: The difference from Example 1 is that the carbon fiber plate containing polyimide is placed in a vacuum oven containing a mixture of triethoxy-1H, 1H, 2H, 2H-perfluorodecylsilane, ethanol and deionized water, and heated at 200°C for 3h to obtain a carbon fiber plate containing polyimide without PDVB. Other steps are the same.
[0041] Comparative Example 4: The difference from Example 1 is that the carbon fiber board is directly placed in a vacuum oven containing a mixture of triethoxy-1H, 1H, 2H, 2H-perfluorodecylsilane, ethanol and deionized water, and heated at 200°C for 3h to obtain a carbon fiber board containing only PDVB without polyimide, and the rest are the same.
[0042] Performance Test:
[0043] 1. Elongation and solder paste offset performance test
[0044] After printing is completed, the SPI equipment is used to measure the offset of the solder paste printed by the carbon fiber material printing template prepared in the embodiment and the comparative example falling on the PCB pad position, and a microcomputer-controlled electronic universal testing machine (ETM105D) is used. At a temperature of 23±2°C and a humidity of 50±10%RH, according to GB / T 1040.1-2018, GB / T 1040.3-2006, GB / T 228.1-2021, and GB / T3362-2005, the carbon fiber board obtained in the embodiment and the comparative example (test width of 15 mm, test rate of 5 mm / min) and 304 stainless steel purchased on the market are compared and tested, and the results are shown in Table 1.
[0045] Table 1
[0046]
[0047] It can be seen from Table 1 that the solder paste offset of the carbon fiber material printing template of Example 1 is the smallest, and the elongation A50mm of the carbon fiber board of the example is ≤2.6%. When printing precision instruments, higher requirements are placed on the dimensional stability of the material. A smaller elongation can make the material deform less when subjected to external force, thereby maintaining better dimensional stability. Overall, the example has better performance.
[0048] 2. Self-cleaning test
[0049] The ceramic and carbon fiber plates prepared in the examples and comparative examples were tilted at 20° for self-cleaning test. Standard sand (0.2 g) specified in ISO 679 was sprayed on the ceramic and carbon fiber plates, and then 0.7 mL of deionized water was dripped in with a syringe for 3 seconds, standard sand (0.5 g) was sprayed, and then deionized water (1.5 mL) was dripped in with a syringe for 5 seconds. The carbon fiber plates of Examples 1-3 and the ceramic surfaces of the examples slid down with the water droplets, and the dust was completely taken away. Finally, there were no particles or droplets on the surface, while there were no particles on the surface of Comparative Example 1, and droplets remained, there were particles and droplets on the surface of Comparative Example 2, there were particles and droplets on the surface of Comparative Example 3, there were no particles on the surface, and droplets remained, and there were no particles on the surface of Comparative Example 4, and droplets remained.
[0050] The hydrophobicity test was performed on the carbon fiber plate of Example 1 and Comparative Example 2 using an optical contact angle meter. The contact angle of Example 1 was 155.5°, and that of Comparative Example 2 was 70±1°.
[0051] 3. Wear test
[0052] The ceramic prepared in Example 1 and the carbon fiber plates prepared in Examples and Comparative Examples were tested for wear using a vertical multifunctional friction and wear tester MFT-5000 according to ASTM G203 standard. The results are shown in Table 4.
[0053] <![CDATA[Wear amount under 500N / cm 3 > Example 1 Ceramic 0.31 Example 1 Carbon fiber board 0.44 Example 2 Carbon fiber plate 0.48 Example 3 Carbon fiber plate 0.45 Comparative Example 1 Ceramic 0.37 Comparative Example 2 Carbon Fiber Plate 0.55 Comparative Example 3 Carbon Fiber Plate 0.58 Comparative Example 4 Carbon Fiber Plate 0.53
[0054] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A carbon fiber material printing template, characterized in that: The invention comprises a ceramic outer frame and a carbon fiber composite material inner net; the ceramic outer frame is made of zirconia ceramic and polyimide-PDVB nanocomposite material; the preparation method of the ceramic outer frame comprises the following steps: applying a suspension on the zirconia ceramic, heating the ceramic to obtain a ceramic containing polyimide, mixing divinylbenzene, azoisobutyronitrile and ethyl acetate to obtain a mixed solution, and placing the ceramic containing polyimide into the mixed solution to obtain a ceramic containing polyimide-PDVB nanocomposite material.
2. The carbon fiber material printing template according to claim 1, characterized in that: The preparation method of the carbon fiber composite material inner net is to laser cut a carbon fiber plate containing a polyimide-PDVB composite material into carbon fiber warp and weft lines, lay them flat, and press the intersections of the carbon fiber warp and weft lines.
3. The carbon fiber material printing template according to claim 1, characterized in that: The polyimide-PDVB nanocomposite material is prepared from the following raw materials: 2,2′-bis(trifluoromethyl)benzidine, dimethylacetamide, 4,4′-(hexafluoroisopropylidene)diphthalic anhydride, [(3-triethoxysilyl)propyl]succinic anhydride, tetraethyl orthosilicate, an auxiliary agent, divinylbenzene, azoisobutyronitrile and ethyl acetate, wherein the auxiliary agent is nanocarbon and graphene, and the auxiliary agent is 1-3 parts of nanocarbon and 1-3 parts of graphene in parts by weight.
4. The carbon fiber material printing template according to claim 1, characterized in that: The polyimide-PDVB nanocomposite material is prepared from the following raw materials in parts by weight: 5-15 parts of 2,2′-bis(trifluoromethyl)benzidine, 90-180 parts of dimethylacetamide, 10-20 parts of 4,4′-(hexafluoroisopropylidene)diphthalic anhydride, 1-5 parts of [(3-triethoxysilyl)propyl]succinic anhydride, 1-5 parts of tetraethyl orthosilicate, 2-6 parts of auxiliary agents, 1 part of divinylbenzene, 0.06 parts of azoisobutyronitrile and 45 parts of ethyl acetate.
5. The carbon fiber material printing template according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: 2,2′-bis(trifluoromethyl)benzidine and dimethylacetamide are stirred with argon at 25° C., 4,4′-(hexafluoroisopropyl)diphthalic anhydride is added to a flask, the obtained solution is stirred with argon at 25° C. to prepare a polyamic acid solution, [(3-triethoxysilyl)propyl]succinic anhydride is added, and the [(3-triethoxysilyl)propyl]succinic anhydride end-capped polyamic acid is synthesized by stirring, tetraethyl orthosilicate, ethanol and ammonia solution are added, and silica sol is obtained by stirring, the silica sol is added to the end-capped polyamic acid solution, and the suspension is obtained by stirring, an auxiliary agent is added to the suspension, the suspension is coated on a carbon fiber board, and the carbon fiber board containing polyimide is heated to obtain the carbon fiber board, divinylbenzene, azoisobutyronitrile and ethyl acetate are ultrasonically mixed to obtain a mixed solution, and the carbon fiber board containing polyimide is placed in the mixed solution for reaction to obtain a carbon fiber board containing a polyimide-PDVB composite material.
6. The method for preparing a carbon fiber material printing template according to claim 5, characterized in that: The 2,2′-bis(trifluoromethyl)benzidine and dimethylacetamide are stirred with argon for 20-40 minutes, tetraethyl orthosilicate, ethanol and ammonia solution are added and stirred at 50-60° C. for 1-2 hours, and silica sol is added to the end cap polyamic acid solution and stirred at 50-60° C. for 2-4 hours.
7. The method for preparing a carbon fiber material printing template according to claim 5, characterized in that: The thickness of the suspension coated on the carbon fiber plate is 1-3 μm.
8. The method for preparing a carbon fiber material printing template according to claim 5, characterized in that: The carbon fiber plate containing polyimide is placed in the mixed solution and the reaction temperature is 100-150° C. to obtain a carbon fiber plate containing a polyimide-PDVB composite material.
Citation Information
Patent Citations
Printing template of an smt process and method of coating it
CN101268724A
An SMT printing template
CN104191855B
Electronic product frame structure made of carbon fiber ceramic composite material and manufacturing method of the structure
CN105827759A
Epoxy resin composite material containing polyamide coating
CN114987025A